2023
DOI: 10.1029/2023ja031467
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Some Longstanding Issues in Far Ultraviolet Remote Sensing: A Self‐Consistent Analysis of the GUVI and SEE Observations on the TIMED Mission

Jianqi Qin

Abstract: Far Ultraviolet (FUV) remote sensing has been used in aeronomy missions as a powerful means to measure the temperature and compositions in the upper atmospheres of terrestrial planets. However, despite decades of continual development, outstanding challenges remain in this field. Particularly, there is currently a lack of methods for the examination and improvement of the data products in FUV remote sensing. As a result, longstanding issues exist in many of those data products. Here we demonstrate that a self‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
(302 reference statements)
0
1
0
Order By: Relevance
“…They found that the Q EUV measurements by SEE need to be lowered by ∼30% to reconcile the GUVI and SEE measurements. More recently, Qin (2024) examined the accuracies of the GUVI and SEE data products through a self-consistent analysis and modeling of the airglow emissions acquired from all the five GUVI channels. The author found that SEE overestimates Q EUV by ∼25%, which is highly consistent with the results shown in Figure 8.…”
Section: Geometric Extrapolation To Marsmentioning
confidence: 99%
“…They found that the Q EUV measurements by SEE need to be lowered by ∼30% to reconcile the GUVI and SEE measurements. More recently, Qin (2024) examined the accuracies of the GUVI and SEE data products through a self-consistent analysis and modeling of the airglow emissions acquired from all the five GUVI channels. The author found that SEE overestimates Q EUV by ∼25%, which is highly consistent with the results shown in Figure 8.…”
Section: Geometric Extrapolation To Marsmentioning
confidence: 99%